Criminal forms of high frequency trading on the financial markets. (3rd April 2015) - Fisher, Jonathan; Clifford, Anita; Dinshaw, Freya; Werle, Nicholas
Abstract : Section 90(1) of the UK Financial Services Act 2012 criminalises the creation of a false or misleading impression in financial markets. In the absence of any criminal prosecutions under this section to date, the potential scope of the new criminal offence remains moot especially in the context of high frequency trading where market participants develop trading strategies using algorithmic computer programs which are designed to profit from very small movements in share prices which have been generated by a series of high-speed purchases and sales, or short sales and subsequent purchases. Notwithstanding the fact that section 90 does not reference high frequency trading, the statutory language is sufficiently broad to capture high frequency trading strategies where it can be shown that they have created a false or misleading impression as to the price or value of the company share which has been, or is being, traded.